Novel Approaches in Fabrication and Integration of Nanowire for Micro/Nano Systems. (7th November 2022) - Adam, Tijjani; Dhahi, Thikra S.; Gopinath, Subash C. B.; Hashim, Uda
Abstract: Nanowires have been utilized widely in the generation of high-performance nanosensors. Laser ablation, chemical vapor, thermal evaporation and alternating current electrodeposition are in use in developing nanowires. Nanowires are in a great attention because of their submicron feature and their potentials in the front of nanoelectronics, accelerated field effect transistors, chemical- and bio-sensors, and low power consuming light-emitting devices. With the control of nanowire size and concentration of dopant, the electrical sensitivity and other properties of nanowires can be tuned for the reproducibility. Nanowires comprise of arrays of electrodes that form a nanometer electrical circuit. One of advantages of nanowires is that they can be fabricated in nanometer-size for various applications in different approaches. Several studies have been conducted on nanowires and researchers discovered that nanowires have the potential in the applications with material properties at the nanometer scale. The unique electrical properties of nanowires have made them to be promising for numerous applications. Nowadays, for example, MOS field-effect transistors are largely used as fundamental building elements in electronic circuits. Also, the dimension of MOS transistors is gradually decreasing to the nanoscale based on the prediction made by Moor's law. However, their fabrication is challenging. This review summarized different techniques in the fabrication of nanowires, global nanowire prospect, testing of nanowires to understand the real electrical behavior using higher resolution microscopes, and brief applications in the detection of biomolecules, disease such as corona viral pandemic, heavy metal in water, and applications of nanowires in agriculture.